(untitled) (Baghdad Science Journal, 2024)
The CuCo2O4 compound has been prepared by the Sol-gel method starting with cobalt sulfate CoSO4.7H2O and copper nitrate, using Pectin as a stabilizer. The samples have been annealed at different temperatures (400-1000°C) to produce CuCo2O4. Thermo-gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), Scanning Electron Microscope (SEM) and X-ray diffraction (XRD) techniques have been used to characterize the compositional properties of the prepared compound. The optimum temperature for synthesis is found at 600°C. According to X-ray diffraction patterns, CuCo2O4 spinel has a face-centered cubic crystal (FCC) and belonged to the Fd3m space group. The lattice constants, unit cell volume, and number of formulas have been calculated. Their values are 8.044 Å, 520.49 Å3, and 8, respectively. It is found that the grain size of the compound is 17.4nm. The experimental results for d corresponded to the reference card values with an accuracy of 99.5% as a minimum. The theoretical and experimental density of the prepared compound have been calculated and the results are approximately identical. The differential thermal analysis curves showed five thermal effects, the most important of which are the exo-thermal peak at 390°C and end-thermal peak at 740°C, which indicate to start forming and decomposition of Cu respectively. The IR spectroscopy encouraged our results during the bonding vibrations of Co-O, Cu- O.